2010
DOI: 10.1002/jsfa.4025
|View full text |Cite
|
Sign up to set email alerts
|

Birds select conventional over organic wheat when given free choice

Abstract: The results of this study suggest that the current dogma that organic food is preferred to conventional food may not always be true, which is of considerable importance for consumer perceptions of organically grown food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Siwalan brown sugar is favored by the birds possibly because of the flavor of this sugar. Birds have individual preferences for foods based on the taste, habits, food placement, texture, size, shape and colour (McKenzie and Whittingham, 2010). Taste may also play a role in sugar type preferences (Hollo- Matson and Koutsos (2006) stated that tastes and specific appetites may sometimes drive the feed consumption.…”
Section: Preferences On Type Of Brown Sugar Solutionsmentioning
confidence: 99%
“…Siwalan brown sugar is favored by the birds possibly because of the flavor of this sugar. Birds have individual preferences for foods based on the taste, habits, food placement, texture, size, shape and colour (McKenzie and Whittingham, 2010). Taste may also play a role in sugar type preferences (Hollo- Matson and Koutsos (2006) stated that tastes and specific appetites may sometimes drive the feed consumption.…”
Section: Preferences On Type Of Brown Sugar Solutionsmentioning
confidence: 99%
“…For example, egg-laying kakapo hens select a diet that apparently is deficient in essential fatty acid even when foods that can meet the requirement are available (Body and Powlesland, 1990). Birds have individual preferences for foods based on taste, habits, food placement, texture, size, shape and colour (Brue, 1994;McKenzie and Whittingham, 2010). Avian taste buds are found in much lower numbers than those of mammals in the oral cavity.…”
Section: Determination Of Bird Nutrient Requirementsmentioning
confidence: 99%
“…It has been shown that some birds choose conventional seeds when given the choice (in relation to organic food). This could be explained either because conventional seeds have a higher protein rate or because of the animals’ previous feeding habits (McKenzie and Whittingham, ). Different kinds of cooking processes are also available: pelletizing and extrusion.…”
Section: Veterinarian Perspectivesmentioning
confidence: 99%
“…Avoiding the presence of Fusarium mycotoxins in food is very important, thus organic food is perceived as “food without chemistry” of higher quality than conventional [11,12]. In the literature, you can find analyses on this issue comparing wheat form organic and conventional cropping systems [13,14,15,16,17]. Mäder et al [18] analyzed Fusarium metabolites, deoxynivalenol (DON) and nivalenol (NIV), content in wheat grain produced in a 21-year conventional and organic agrosystems.…”
Section: Introductionmentioning
confidence: 99%